PENGGUNAAN METODE PEMROGRAMAN BERORIENTASI OBJEK (OBJECT ORIENTED PROGRAMMING) PADA BAHASA PEMROGRAMAN - Priatno Priatno (LPPM Universitas Bina Sarana Informatika, 2008)
The bigger a system applied in a company or an institution the greater the problems it causes. Such condition requires an establishment and development of computer based programming as one alternative solution to the problems. Object Oriented Programming is a programming application, which is widely used among programmers when they build a programming application to solve problems faced by a computerized system.